Survival Analysis of Hemodialysis Patients - Efri Tri Ardianto; Hari Basuki Notobroto; Windhu Purnomo (Intelektual Pustaka Media Utama, 2016)
Survival analysis as a collection of statistical procedures for analyzing the data that its outcome variable was the time to occurrence of an event. Kaplan-Meier method is a type of survival analysis technique, this method is often called the Product Limit Method. Chronic Kidney Disease (CKD) became one of the public health problem throughout the world, including Indonesia. The number of hemodialysis patients has increased every year and have an impact on increasing the number of death in General Hospital Ibnu Sina Gresik. This study was determine the survival of hemodialysis patients using Kaplan-Meier analysis techniques. Non-reactive research with a retrospective cohort using the calculations right censoring. 155 population were taken randomly and sample size of 111. Data were collected using a checklist. The estimated survival time of female, adult age, further education, patients work, patients without insurance, patients with normal nutritional status, patients with a history of disease, patient with hypertention and patient with diabetic had a better survival time. The insurance status, nutritional status, hypertension, and diabetes mellitus were significant difference to the survival time (p-value <0.05). It was necessary special treatment for CKD patients through giving information, education to families and patients to maintain healthy lifestyle.